Synchrony of Choice of the Departments in Tourism and Hospitality with Gender Stereotyped Careers - Dewa Gde Ngurah Byomantara; Arifuddin Arifuddin (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
The choice of jobs portraits the community’s mindset. However, the consistency of Balinese mindset to gender-stereotyped careers and the distribution of the students' genders in each department in Bali Hospitality and Tourism Institutes or higher educations have not been reported. The present study aimed at examining the proportions of the students' genders in each department in Bali Hospitality and Tourism Institutes or higher educations and the community mindset regarding the choice of jobs based on gender. 1,656 students of the three Tourism and hospitality institutes in Bali took part. Data were based on the entrance test and questionnaire (Google Form) analyzed with iterative analysis (Yin, 2010). Hospitality Management, Food and Beverage Service Management, Hospitality, Food Service Management, and Tourism Management and Hospitality Administration are the favorite departments. Two of the six departments, Hospitality Management and Food and Beverage Service Management are the two most favorite departments. On the contrary, four least favorite departments are Travel Business Management, Tourism Destination, Convention and Exhibition Management and Spa Management. All departments of the Bali Tourism and Hospitality institutes, females are more dominant. It shows that Balinese community are flexible and hold the same mindset regarding gender-stereotyped careers, such as Food and Beverage Service Management, Hospitality, and Food and Service Management.